Modeling of financial and budgetary flows of the region - Rekunenko, Ihor; Cherednichenko, Dmytro; Olkhovyk, Ivan; Рекуненко, І. І.; Чередніченко, Д. С.; Ольховик, І. В. (Харківський національний автомобільно-дорожній університет, 2025)
Purpose. To investigate the impact of socio-economic, fiscal, and institutional factors on the formation of financial and budgetary flows in Ukrainian regions under crisis conditions. Research Methodology. The study applies a panel data econometric model with fixed effects covering the period 2020–2024. The model incorporates the following variables: revenues, expenditures, gross regional product, population, foreign direct investment, intergovernmental transfers, and international grants. The data sources include official statistics from the State Statistics Service of Ukraine, the Ministry of Finance of Ukraine, and international organizations. Results. The study demonstrates that regional revenues and intergovernmental transfers are the main positive drivers of net budgetary flows, while expenditures exert a consistent negative impact. The significant role of foreign direct investment and international grants in maintaining fiscal balance in economically active regions is also confirmed. Notable inter-regional differences in fiscal resilience were identified, with central and western regions outperforming others. Scientific Novelty. The article develops a comprehensive econometric model of regional financial and budgetary flows in Ukraine, incorporating crisis-related factors and external support mechanisms, thus enabling more precise evaluation of regional budget dynamics under conditions of iinstability. Practical Significance. The findings can be utilized by government bodies, local authorities, and analytical think tanks to design effective fiscal policies, strategically allocate transfers, and plan regional recovery in the post-crisis period.
Mоделювання фінансових і бюджетних потоків регіону
Keywords: regional budgetary flows; fiscal modeling; panel data analysis; Ukraine; financial resilience; public finance; intergovernmental transfers; регіональні бюджетні потоки; фіскальне моделювання; аналіз панельних даних; Україна; фінансова стійкість; публічні фінанси; міжбюджетні трансферти; 336.14; 336.1; 332.1; https://doi.org/10.30977/PPB.2226-8820.2025.34.237